Pregnancy health literacy among teenagers in Kaysone district, Savannakhet Province, Lao PDR - Phonevilai Santisouk; Visanou Hansana; Nguyen Thanh Huong (Taylor & Francis Group, 2020)
Background Pregnancy health literacy (PHL) among teenagers is considered a major protective factor for teenage pregnancy. In Lao PDR, 18% of girls aged 15-19 have begun childbearing and 15% of maternal deaths occur to teenage girls, particularly in rural areas. Objective The aim of this study was to describe PHL and its related factors among teenagers in Kaysone district. Method This was a cross-sectional study conducted at Oudomvilay and Kheuakhaokat in Kaysone district in January 2019. The Teenage Pregnancy Health Literacy (TPHL) score was collected via face to face interviews covering 33 items with 262 adolescents. Calculation of the TPHL index score was based on the European Health Literacy Survey (HLS-EU) index formula. The TPHL index was also based on the HLS-EU standard level and descriptive statistics were used to explain the score and levels. Descriptive analyses were performed to analyse the individual, family, peer and school variables and to investigate level of TPHL and linear regression was used to identify factors related to TPHL. Results The overall score for TPHL was a mean of 27/50. Most (60%) of the adolescents had problematic TPHL levels and only 0.4% had excellent TPHL levels. TPHL was positively and significantly associated with living in urban areas (β = 2.42; p = 0.002), higher education (β = 2.93; p = 0.004), schooling (β = 0.96; p = 0.018), being single (β = 2.9; p = 0.029) and attending classes where sex education content was included (β = 4.72; p < 0.001). Conclusion Low TPHL scores show the importance of improving sex education for adolescents as a means of increasing TPHL for better health outcomes in Lao PDR.